The Concept of Education Religion, Philosophy, Ethics and Science - Abdulhalim Hamid Salih Hamid; Hafidha Zekkour; Triyo Supriyatno (Indonesian Journal of Islamic Education Studies (INJURIES), 2024)
This study explores the interplay between religion, philosophy, ethics, and science, emphasizing their interconnected roles in fostering a comprehensive understanding of humanity and the natural world. The research highlights the historical and contemporary relationships between these domains, analyzing how religion provides a moral framework, philosophy bridges critical inquiries, ethics regulate scientific advancements, and science offers practical solutions. Employing historical analysis, philosophical critique, and comparative methods, the study addresses key ethical challenges such as artificial intelligence, cloning, and environmental sustainability. The findings suggest that integrating these fields fosters sustainable development and promotes balanced societal growth by aligning technological progress with spiritual and ethical values. The study concludes by recommending interdisciplinary approaches to address global ethical dilemmas effectively. Keywords: Religious Education, Philosophy, Ethics, Science, Interdisciplinary Integration